PENGARUH PENAMBAHAN SUKUN MUDA (Artocarpus communis) TERHADAP MUTU FISIK, KADAR PROTEIN, DAN KADAR AIR ABON LELE DUMBO (Clarias gariepinus) - Ninna Rohmawati (Poltekkes Kemenkes Yogyakarta, 2016)
Introduction: Protein Energy Malnutrition (PEM) is still a major general nutrition problems experienced at children aged under five years (toddlers). The results of Riskesdas 2013, prevalence of malnutrition and malnutrition in toddlers 19.6 % it means of malnutrition and severe malnutrition in Indonesia is still a public health problems. Fish as source of protein can be used as an alternative food sources PEM problem solving. Sukun is expected to improve the quality of the abon (nutritional value and texture). The objective of this research was to analyze effect of addition of sukun toward physical quality, protein content, and water content of catfish abon. Methods: This research was used quasi experimental design. The design was using posttest only control designed to 2 replication a standard treatment with three and one control. Physical quality using hedonic scale tests. Chemical analysis of protein levels with semi microkjeldahl test and water content using cawan method. The results of the analysis using Friedman test. If the results was significant then proceeded to Wilcoxon Signed Rank Test. Results: Addition of sukun with different proportions in any treatment can affect physical quality (sense, color, flavor, texture) modification abon. There is a trend of decrease in protein levels with increasing proportion of sukun added to abon (33.79% - 39.64%). There is a tendency of an increase in water content with increasing proportion of sukun added to modification abon (4.83% to 5.9%). Conclusions: Right proportion of addition of sukun in abon modifications is P1 (abon from catfish with additional sukun 20 %). Keywords: sukun, physical quality, protein content, water content, abon.